Improved signal‐to‐noise ratio estimation algorithm for asymmetric pulse‐shaped signals. Issue 14 (1st September 2015) - Shao, Huaizong; Wu, Di; Li, Yang; Liu, Wuling; Chu, Xiaoli
Abstract : The split‐symbol moment estimation (SSME) algorithm is a conventional method to estimate the signal‐to‐noise ratio (SNR) in communication systems for M ‐ary phase shift keying signals. However, the conventional SSME is based on the assumption of symmetric pulse‐shaping waveforms, and becomes no longer proper when the shaping pulse is asymmetric. In this study, the authors propose a modified SSME algorithm for asymmetric pulse‐shaped signals, based on an odd‐even symbol splitting approach. Simulation results show that the modified SSME outperforms the conventional SSME for both symmetric and asymmetric pulse‐shaped signals in terms of SNR estimation accuracy.